The vegetation, climate, and fire history of a mountain steppe: A Holocene reconstruction from the South Caucasus, Shenkani, Armenia. (15th October 2020) - Cromartie, Amy; Blanchet, Claire; Barhoumi, Chéïma; Messager, Erwan; Peyron, Odile; Ollivier, Vincent; Sabatier, Pierre; Etienne, David; Karakhanyan, Arkady; Khatchadourian, Lori; Smith, Adam T.; Badalyan, Ruben; et al.
Abstract: Steppe and grassland ecosystems constitute important biomes that are influenced by multiple factors such as climate, human activity, and fire. Yet how these factors have influenced the plant composition of these biomes through time continues to be understudied. This paper investigates how these mechanisms have transformed the steppe landscape recorded at the mire site of Shenkani, Armenia. This highland site, located in the South Caucasus, has a long human history of permanent settlements near the core site starting at 5500 cal. BP. A variety of biological and geochemical proxies, including pollen, non-pollen palynomorphs, macro-charcoal, 14 C age model, X-ray fluorescence, loss-of-ignition, magnetic susceptibility, and a quantitative climate reconstruction inferred from pollen, are utilized in this paper. We find that this area has remained a steppe with small stands of trees throughout the duration of the Holocene. Changes in steppe plant composition primarily occur between semi-desert steppes (Chenopodiaceae), grassland steppes (or Poaceae dominated meadow-steppes), and mixed steppes with forest patches. In this record, two phases of local grassland expansion occurred between 9500 and 7000 cal. BP and 2500–1000 cal. BP, which covaried with local fire events. These grassland steppes were sustained until tree encroachment led to a more mixed steppe landscape around 7000 cal. BP and again at 1000 cal. BP. Climate, primarily precipitation, is the main driver of this persistent steppe landscape and the plant compositional shifts within it. However, fire and human activities contributed to steppe maintenance. Highlights: A 10, 240 year-old sequence from Shenkani, Armenia documents a persistent Holocene steppe. Changes in steppe plant composition occur between semi-desert, grassland, and mixed steppes with forest patches. Poaceae dominated grasslands covary with fires that limit tree and shrub encroachment. The mid- to late Holocene transition is characterized by drops in Betula and declines in distant arboreal pollen.